PERENCANAAN PENENTUAN KEBUTUHAN STI PADA PT INDONESIA MAGMA CHAIN - Setiawan, Ari Andika; Sutomo, Erwin; Hananto, Valentinus Roby (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Indonesia Magma Chain is a chain and conveyor maker company located in Demak, Central Java. PT Indonesia Magma Chain already invested in system and information technology (SIT) to manage reservations and sales transactions. But it can not run well, because the company is not doing a good plan at the time of SIT investment, such as providing applications that can not accommodate the needs and business procces of the PT Indonesia Magma Chain. Based on the above issues, the planning indentifying of the SIT requirements at PT Indonesia Magma Chain using method from John Ward and Joe Peppard, and SWOT analysis that will produce an application portfolio that is divided into 4 quadrants of McFarlan Strategic Grid and a road map of the SIT for 2 years starting from 2017 to 2018.